Polemic of Gratification Attitude (Political Bride Price) in the Implicit Implementation of People's Feast in Indonesia - Monita, Tria; Lestari, Alika Ayu; Yustikarini, Hesty Dian (Law Research Review Quarterly, 2018)
People's party is a manifestation of democracy which is considered the cleanest. In practice, the people's party turned out to form competition in fighting for political office. This competition has had an impact on the rise of fraud. This phenomenon is like a culture that has taken root in Indonesian society. From time to time the forms of cheating carried out increasingly diverse, ranging from the "dawn attack" to the Mahar Politics gave a new color in the implementation of the people's party. In fact, the regulation of the People's Party has been stated normatively in Law Number 7 of 2017 concerning General Elections. Ironic indeed, in the election alone there had been a lot of fraud let alone the implementation of the government. The negative specter that is caused, makes people uncomfortable seeing prospective leaders actually implies acts that tend to be immoral and justifies any means to smooth their interests. So that the question arises whether the leader is suitable to be elected or when he has been elected will actually cause harm to the people and even the State? This will be a puzzle both in the world of politics and in the minds of the people until the people are dashed in wanting a leader who is actually appropriate and clean. Various phenomena that surround the implementation of the election cause a loss of people's trust in the government, especially the leaders. In addition, losses from election crimes also cause consequences in terms of state finances.